Influence of additive nano calcium carbonate (CaCO3) on SAE 10W-30 engine oil: A study on thermophysical, rheological and performance - Dany Ardymas Kurniawan; Poppy Puspitasari; Ahmad Atif Fikri; Avita Ayu Permanasari; Jeefferie Abd. Razak; Diki Dwi Pramono (Mechanical Engineering for Society and Industry, 2024)
Researchers have used nanomaterials as additives in base oil to improve its specifications, especially to minimize wear and friction during its applications. In this study, calcium carbonate (CaCO3) nanoparticles were selected as an additive to serve as a protective layer between components and anti-wear properties. In this study, calcium carbonate (CaCO3) nanoparticles were selected as an additive to serve as a protective layer between components and anti-wear properties. Nano lubricant samples were prepared using mass variations of CaCO3 and SAE 10W-30 base oil with concentrations of 0.05, 0.1, 0.15, and 0.2%, then homogenized. The nanolubricant samples obtained were analyzed for thermophysical, rheological properties and lubricant performance with the addition of nano CaCO3 in improving the wear resistance of FC25 cast iron. The results of thermophysical and rheological properties analysis suggest that the nanolubricant has better tribological properties compared to base lubricants. The highest values of thermal conductivity, density, and viscosity (40 °C) are 0.139 W/m.K, 812.203 kg/m3, and 106 mPa.s (40 °C). Meanwhile, the highest CoF, disc mass loss, and surface roughness of nanolubricant are 0.0706, 0.0037 grams, and 0.50 µm, respectively. These results indicate that the greatest wear-reducing agent is from the nanolubricant with the addition of CaCO3 nanopowder additives at 0.1 wt% concentration. These results are expected significant insights into the advancement of nano technology-based lubricants in the future.